Evolution what the fossils say and why it matters - Prothero, Donald R. (Columbia University Press, 2017)
"Over the past twenty years, paleontologists have made tremendous fossil discoveries, including fossils that mark the growth of whales, manatees, and seals from land mammals and the origins of elephants, horses, and rhinos. Today there exists an amazing diversity of fossil humans, suggesting we walked upright long before we acquired large brains, and new evidence from molecules that enable scientists to decipher the tree of life as never before. The fossil record is now one of the strongest lines of evidence for evolution, and yet it continues to come under attack by present-day creationists and advocates of Intelligent Design for not supporting the theory of biological evolution. With this engaging and richly illustrated book, leading paleontologist Donald R. Prothero sets the record straight." "Prothero weaves an entertaining though intellectually rigorous history out of the transitional forms and series that dot the fossil record. Beginning with a brief discussion of the nature of science and the "monkey business of creation-ism," Prothero tackles subjects ranging from flood geology and rock dating to neo-Darwinism and macroevolution. He covers the ingredients of the primordial soup, the effects of communal living, invertebrate transitions, the development of the backbone, the reign of the dinosaurs, the mammalian explosion, and the leap from early primates to Homo sapiens, Prothero pays particular attention to the recent discovery of "missing links" that complete the fossil timeline and the controversy among contemporary scientists over the mechanisms of evolution."--Book jacket.